Selected metabolic changes after extreme endurance physical exercise by the example of marathon and ultra - marathon runners - Uzdzicki, Artur; Malas, Malwina; Przybylski, Tomasz; Turoń-Skrzypińska, Agnieszka; Szylinska, Aleksandra; Ciosek, Zaneta; Ptak, Magdalena; Dutkiweicz, Grazyna; Rotter, Iwona (Journal of Education, Health and Sport, 2018)
A popularity of marathons and ultramarathons is growing every year. Attending a marathon can cause a variety of biochemical changes. It is crucial to determine which changes in blood tests are of clinical significance, and what recommendations should be given to the patient. Here the most frequent changes are presented, as described in literature.